2010
DOI: 10.1111/j.1365-2206.2010.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the care effects of multiple factors on the educational achievement of children looked after at home and away from home: an investigation of two Scottish local authorities

Abstract: This paper reports the findings of a research project which explored the care factors that influence the educational achievement of looked‐after children. The project was innovative because it focused on children looked after at home and away from home. A mixed‐methods strategy was adopted to analyse data from two large Scottish local authorities. The project developed, what is to date, the largest dataset which includes variables for one‐fifth of children discharged from care in Scotland over a 5‐year period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…Their paths into state care, the early family experiences that have resulted in their admission to care, the timing of this admission and the quality of their care experience reflect widely diverse trajectories and backgrounds (Pinkerton, 2000). However, when outcomes for young people in care are examined, a more consistent picture emerges, with research conducted over the last three decades highlighting a disturbing trend of poor educational achievement, poor physical, mental and general well-being, homelessness, criminality, unemployment, teenage parenting and poor social networks (Bilson, Price, & Stanley, 2010;Dixon, 2008;Dumaret, Donati, & Crost, 2011;Martin & Jackson, 2002;McAuley & Davis, 2009;McClung & Gayle, 2010;McCrystal & McAloney, 2010). A number of studies have focused on the mental health status and needs of young people in the care system and at the point of graduation from residential care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their paths into state care, the early family experiences that have resulted in their admission to care, the timing of this admission and the quality of their care experience reflect widely diverse trajectories and backgrounds (Pinkerton, 2000). However, when outcomes for young people in care are examined, a more consistent picture emerges, with research conducted over the last three decades highlighting a disturbing trend of poor educational achievement, poor physical, mental and general well-being, homelessness, criminality, unemployment, teenage parenting and poor social networks (Bilson, Price, & Stanley, 2010;Dixon, 2008;Dumaret, Donati, & Crost, 2011;Martin & Jackson, 2002;McAuley & Davis, 2009;McClung & Gayle, 2010;McCrystal & McAloney, 2010). A number of studies have focused on the mental health status and needs of young people in the care system and at the point of graduation from residential care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from other countries (e.g. Scotland, Australia and Sweden) also finds that children in out-of-home placement are academically vulnerable (Vinnerljung et al 2005;Cashmore et al 2007;McClung & Gayle 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, research over several decades from many countries has shown a high educational disadvantage among the child welfare population. Compared with the general population, child welfare recipients tend to perform poorly in school (Iversen et al 2010;McClung & Gayle 2010;Berlin et al 2011), and relatively few obtain higher education degrees (Cheung & Heath 1994;Jackson & Cameron 2011;Daehlen 2015). Many also lack a high school diploma or an equivalent upper secondary education (Vinnerljung et al 2005;Courtney & Dworsky 2006).…”
Section: Introductionmentioning
confidence: 99%